[Killer Whale Performance at Seven Seas Marine Life Park] (1965)
Photograph of a killer whale performance at the Killer Whale Stadium, Seven Seas Marine Life Park in Arlington, Texas. Newtka, the killer whale, can be seen in the aquatic pool, facing the two trainers who are standing on a platform within the stadium. A castle-themed backdrop is present behind the platform. Orchin, the Seven Seas mascot, is also standing on the platform nearby the trainers.